Teachers Acting Critically Upon the Curriculum: Innovations that Transform Teaching - Clavijo Olarte, Amparo; Guerrero Melo, Carmen Helena; Torres Jaramillo, Claudia; Ramírez Galindo, Luz Maribel; Torres Mesa, Nelly Esperanza (Íkala, Revista de Lenguaje y Cultura, 2004)
This article describes the results of an interpretative qualitative research study in the field of teacher education carried out to identify the processes of innovation in the language curriculum by a group of public school teachers in Bogotá. The innovation process was observed in three stages: identification of the area of intervention, planning, and implementation of the innovation. Data was collected through interviews, videotaped sessions, tutors' reports, and the final documents of the innovation projects. The unit of analysis was the declarative statements of teachers. Two broad aspects of the process of innovation were identified: the process of curricular innovation and the group processes in managing the innovation. In the data analysis three categories emerged that are described in the discussion of findings: shifting the focus of the curriculum,adopting a curricular perspective to support innovative practices, and acting reflectively and dynamically in the innovation. The results tell us that teachers planned and carried out curricular innovations thinking critically about students' needs and interests. They adopted curricular perspectives that helped them construct and support their classroom projects. Finally, teachers acted reflectively during the implementation of the innovation by adjusting their pedagogical practices in order to benefit students' learning and to achieve their institutional goal. Received: 04-05-04 / Accepted: 21-06-04 How to reference this article: Clavijo Olarte, A., Guerrero Nieto, C. H., Torres Jaramillo, C, Ramírez Galindo, L. M. & Torres Mesa, N. E. (2004).Teachers Acting Critically Upon the Curriculum: Innovations that Transform Teaching. Íkala. 9 (1), pp. 11 – 41